Faktor-faktor yang Memengaruhi Tingkat Produktivitas Kopi di Kecamatan Sekincau Kabupaten Lampung Barat - Pardani, Nanda; Rangga, Kordiyana K; Yanfika, Helvi (Universitas Galuh, 2024)
Robusta coffee is one of the plantation commodities which is a superior product in Lampung Province. There has been a decline in robusta coffee productivity in Lampung Province which has had a negative impact on coffee farmers. For this reason, this research aims to analyze the level of coffee productivity and the factors that influence the level of coffee productivity in Sekincau District, West Lampung Regency. This research uses a survey method among coffee farmers in Sekincau District, West Lampung Regency. The respondents in this research were 78 coffee farmers. The data analysis method uses descriptive analysis and multiple linear regression analysis. The results of the research show that the level of coffee productivity in Sekincau District, West Lampung Regency is in the low category with an average of 1 ton/ha. The factors that influence the level of coffee productivity are; farmer motivation, climate, government support, and production facilities, while factors that do not influence the level of coffee productivity are; farmer's age, level of formal education, farming experience, and performance of agricultural instructors.